Monoclonal Antibody to N Protein of Porcine Epidemic Diarrhea Virus - Pan, Xi (Monoclon Antib Immunodiagn Immunother, 2015)
The N gene of porcine epidemic diarrhea virus (PEDV) was amplified by RT-PCR using specific primers, and inserted into the expression vector pCold-I to construct a recombinant plasmid pCold-I-N. The recombinant plasmid was expressed in Escherichia coli BL21 (DE3) under IPTG induction. Then, female BALB/c mice were immunized with the purified recombinant N protein and one strain of hybridoma cells named 2B8 secreting anti-N protein monoclonal antibodies (MAb) was obtained by hybridoma technique. The MAb was specifically reacted with PEDV and identified by Western blot and indirect immunofluorescence assays. This work indicated that the MAb would be a valuable tool as a specific diagnostic reagent for PEDV epidemiological surveys and diagnosis in the future.